On the history of the Bolshevik organizations in Transcaucasia : a lecture delivered at a meeting of active workers of the Tbilisi Party Organization, July 21 - 22, 1935 - Berija, Lavrentij Pavlovič 29.03.1899-23.12.1953 (Foreign Languages Publ. House, 1949)
S. 335-336: Daten aus Stalins Leben, 1902-1917.